Incidence of toxoplasmosis in pregnancy in Campania: A population-based study on screening, treatment, and outcome. (September 2019) - Donadono, Vera; Saccone, Gabriele; Maruotti, Giuseppe Maria; Berghella, Vincenzo; Migliorini, Sonia; Esposito, Giuseppina; Sirico, Angelo; Tagliaferri, Salvatore; Ward, Andrew; Mazzarelli, Laura Letizia; Sarno, Laura; Agangi, Annalisa; et al.
Abstract: Introduction: The aim of this study was to evaluate the incidence of toxoplasmosis infection during pregnancy and to describe the characteristics of the serological status, management, follow-up and treatment. Material and methods: This is a population-based cohort study of women referred for suspected toxoplasmosis during pregnancy from January, 2001 to December, 2012. Suspected toxoplasmosis was defined as positive IgM antibody during pregnancy. Women with suspected toxoplasmosis during pregnancy were classified into three groups: seroconversion, suspected infection, or no infection in pregnancy. Women in the first and second group were treated according to local protocol, and amniocentesis with toxoplasmosis PCR detection and serial detailed ultrasound scans were offered. Neonates were investigated for congenital toxoplasmosis at birth and were monitored for at least one year after birth. Results: During the study period, there were 738, 588 deliveries in Campania. Of them 1159 (0.2%) were referred to our Institution for suspected toxoplasmosis during pregnancy: 183 (15.8%) women were classified as seroconversion, 381 (32.9%) were suspected infection, and 595 (51.3%) were not infected in pregnancy. Neonatal outcome was available for 476 pregnancies, including 479 neonates (3 twins, 473 singletons), out of the 564 pregnancies with seroconversion or suspected infection. 384 (80.2%) babies were not infected at birth and at follow-up, 67 (14.0%) had congenital toxoplasmosis, 10 (2.1%) were voluntary induced termination of pregnancy, 15 (3.1%) were spontaneous miscarriage, and 4 (0.8%) were stillbirth (of which one counted already in the infected cohort). Considering cases of congenital toxoplasmosis, the transmission rate in women with seroconversion was 32.9% (52/158), and in women with suspected infection was 4.7% (15/321). Conclusions: Toxoplasmosis is uncommon in pregnancy with overall incidence of seroconversion and suspected infection in pregnancy of 0.8 per 1000 live births and incidence of congenital toxoplasmosis 0.1 per 1000 live births when applying a strict protocol of screening, follow-up, and treatment. 51.3% (595/1159) of women referred to our center for suspected infection were actually considered not infected.